ANALYSIS OF ROLE OF MEDIA IN DISASTER REPORTING IN PAKISTAN - Iqbal, Muhammad Jawed; Ali, Fatima Masoo; Khursheed, Muhammad Bilal; Saleem, Sadaf (European Scientific Journal, ESJ, 2014)
Disaster brings serious disturbance in the regular activities of a community or society and may cause loss of lives, livelihoods and environmental disorder. These natural disasters are more challenging in the developing countries like India, Pakistan, Nepal, Bhutan, Bangladesh etc., where the impact of these natural disaster is often most devastating. Media is the most important source of information on hazards and disasters for people. From the many decades role of mass media in disaster situation have received less attention by the researchers. Media play an important role in awareness raising and providing information to the masses. This role becomes crucial when it comes to reporting during disasters. The research concluded that currently no code of conduct is available in authorities for reporting the disaster, however some training is provided to the reporters. Currently all the news channels including private and national news channels have self-regulatory code of conduct whereas any code of conduct for natural disaster reporting is still not exists in Pakistan. There is a need that National authorities formulate code of conduct for disaster reporting and disseminate it to the entire news channel so the channels and reporters are bound to cover the disaster within the limitations. At the end Guidelines is provided for Disaster Reporting that may help to alert the officials, emergency and aid organizations, about the specific needs of the affected people in the wake of disaster and in the provision of , accurate, timely, and sensitive information to the public.